Students' Perceptions of Scientific Writing Teaching: Implications for Improving Learning Effectiveness - Purnomo, Eko; Markhamah, Markhamah; Prayitno, Harun Joko; Adhantoro, Muhammad Syahriandi; Rohmadi, Muhammad; Yusof, Norazmie; Alas, Yabit (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze students’ perceptions of scientific writing learning within an advanced and innovative learning framework. The research employed a descriptive quantitative approach using a Likert-scale questionnaire completed by 202 students. The data were analyzed descriptively to obtain the mean, standard deviation, and percentage distribution across five main aspects: participation and interaction, clarity of materials and use of examples, feedback and collaborative guidance, development of academic skills, and time management and variation in innovative learning methods. The results indicate that all aspects achieved mean scores above 3.00 (on a 1–4 scale), which are categorized as high. The highest scores were obtained for teaching method variation (3.14) and material implementation support (3.14), while the lowest score was found in learning time allocation (3.06). Although the majority of students selected the “Agree” category, the proportion of “Strongly Agree” responses remained relatively low (13–17%), suggesting the need for improvement in time allocation, feedback quality, and diversity of examples provided. This study underscores the importance of interactive learning design, consistent use of formative feedback, and the implementation of innovative learning methods to enhance the quality of students’ learning experiences. These findings can serve as a reference for teachers and schools in designing more effective and sustainable scientific writing instruction strategies.